Engineering Performance of Concrete Beams Reinforced with GFRP Bars and Stainless steel (Global Journals of Research in Engineering, 2012)
Corrosion of steel reinforcement is one of the main problems facing the construction industries throughout the world Many methods have been used to minimize the problem but without success Thus more durable reinforcements are highly needed to replace conventional steel Glass Fibre Reinforced Polymer GFRP bars provide a good alternative reinforcement due to its non-corrodible characteristic This paper presents the flexural behaviour of concrete beams each size is 150 x 150 x 900 mm and reinforced with GFRP and stainless steel bars The behaviour of the beams was analysed in terms of their moment carrying capacity loaddeflection cracking behavior and mode of failure The experimental results show that beams reinforced with GFRP bars experienced lower ultimate load lower stiffness and larger deflection at the same load level compared with control beam However the performance of the SSRB Stainless Steel Reinforced Beam reinforced concrete beams improved slightly when compared to Glass Fibre Reinforced Polymer concrete beams
Keywords: GFRP; Stainless Steel; Concrete Beams; Flexural Behaviour; crack width; failure mode